A Randomized, Double-Blind, Placebo-Controlled, Pilot Trial of Individualized Homeopathic Medicines for Cutaneous Warts - Dey, Samit; Hashmi, Shifa; Saha, Sangita; Mandal, Mahakas; Shaikh, Abdur Rahaman; Agrawal, Ekta; Ghosh, Priyanka; Sehrawat, Nisha; Koley, Munmun; Saha, Subhranil (Homeopathy, 2021)
Background Though frequently used in practice, research studies have shown inconclusive benefits of homeopathy in the treatment of warts. We aimed to assess the feasibility of a future definitive trial, with preliminary assessment of differences between effects of individualized homeopathic (IH) medicines and placebos in treatment of cutaneous warts.Methods A double-blind, randomized, placebo-controlled trial (n = 60) was conducted at the dermatology outpatient department of D.N. De Homoeopathic Medical College and Hospital, West Bengal. Patients were randomized to receive either IH (n = 30) or identical-looking placebo (n = 30). Primary outcome measures were numbers and sizes of the warts; secondary outcome was the Dermatology Life Quality Index (DLQI) questionnaire measured at baseline, and every month up to 3 months. Group differences and effect sizes were calculated on the intention-to-treat sample.Results Attrition rate was 11.6% (IH, 3; placebo, 4). Intra-group changes were significantly greater (all p < 0.05, Friedman tests) in IH than placebo. Inter-group differences were statistically non-significant (all p > 0.05, Mann-Whitney U tests) with small effect sizes—both in the primary outcomes (number of warts after 3 months: IH median [inter-quartile range; IQR] 1 [1, 3] vs. placebo 1 [1, 2]; p = 0.741; size of warts after 3 months: IH 5.6 mm [2.6, 40.2] vs. placebo 6.3 [0.8, 16.7]; p = 0.515) and in the secondary outcomes (DLQI total after 3 months: IH 4.5 [2, 6.2] vs. placebo 4.5 [2.5, 8]; p = 0.935). Thuja occidentalis (28.3%), Natrum muriaticum (10%) and Sulphur (8.3%) were the most frequently prescribed medicines. No harms, homeopathic aggravations, or serious adverse events were reported.Conclusion As regards efficacy, the preliminary study was inconclusive, with a statistically non-significant direction of effect favoring homeopathy. The trial succeeded in showing that an adequately powered definitive trial is both feasible and warranted.Trial Registration CTRI/2019/10/021659; UTN: U1111–1241–7340
Keywords: cutaneous warts; dermatological life quality index; homeopathy; randomized controlled trial